Efeitos cardiovasculares e renais de proteínas do látex de Calotropis procera - Monteiro, Manuel Carlos Serra Azul (2015)
Introduction and aim: Calotropis procera (CP) is a laticifer plant adapted in arid and semiarid climates, when mechanically damaged it produces latex. CP in Asia is used in popular medicine. Its rubber fraction is removed cause is high toxic. A protein fraction is separated from the latex of CP, it is (LP). Methodology: After experimental protocol approved to ethic committee in animals (CEPA/UFC n°67/2012), male adults rats (n = 4 till 6 per group) submitted to cardiovascular and renal approaches, using in vivo, ex vivo and in vitro, in order to investigate toxicological and physiological properties of LP. Mean arterial pressure measured (PAM); Renal perfusion from isolated kidney; Histology hematoxylin/eosin (HE); Flow cytometry; Test for inhibition cell growing: MTT. Results: LP showed a hypotensive effect initiated when LP 144 µg/ml injected in jugular of rat, leading a PAM decrease -22% , and falling -29%, 444 µg/ml, both cumulative concentrations with no cardiac frequency or small vascular resistance effects. In Renal perfusion had diminishing of glomerular filtration rate (RFG) (0,1649±0,02734* versus (vs) 0,740±0,02) and electrolytes reabsorption at Na+ (%TNa+) (72,15±4,526* vs 81,30±0,03), and Cl- (%TCl-) (69,31±4,441* vs 77,10±0,29), and K+ (%TK+) (68,51±5,660* vs 74,78±0,14),. versus control and it depended on concentration and time. Already at 30 mg/ml decreased urinary flow only in times of 90 and 120 minutes, however in the same concentration and times had no reduction in% TK +, a phenomena which explained the other one. (HE) showed renal tubules damage at 10 and 30 µg/mL, more severe at 100 µg/ml concentration LP had toxicity added at canine tubular renal cells in culture, Madin Darbin Canine Kidney (MDCK), since 6,25 g/mL, increasing until 200 g/ml concentration. At flow cytometry to 100 µg/ml the most of the cells died by necrosis or late apoptosis. The renal lesions scores measured in histologic laminas proved renal damage induced from LP mainly in tubular renal areas. Conclusion: The toxic effect at kidney perfused tissue, histology (HE), renal perfusion, and MDCK cells could partially explain changes on glomerular filtration and tubular reabsorption, and contributes indirectly hypotension in vivo. More experiments are need for ameliorate the elucidation these mechanisms.